Pengaruh kerapatan terhadap koefisien absorbsi bunyi papan partikel serat daun nenas (Ananas comosus L Merr) (Effect of density on sound absorption coefficient of pineapple leaf fiber particle board (Ananas comosus L Merr)) - Wahyudil Hayat; - Syakbaniah; Yenni Darvina (Department of Physics – Universitas Negeri Padang UNP, 2013)
ABSTRACTThe main objective of this study was to determine the effect of density on board sound absorption coefficient of the particle board pineapple leaf fiber which will be applied as a silencer. Preparation of the sample begins with the separation of basic ingredients, followed by the manufacture of rectangular samples with a size of 9 × 9 × 0.5 cm using a machine felts, then the acoustic characteristics of the specimens were tested using a resonance tube. From the research that has been done can be concluded that at low density the greater the density of the sound absorption coefficient of the particle board pineapple leaf fiber, the greater the coefficient absorbsinya. At high density, the sound absorption coefficient down.Keywords: absorption coefficient, pineapple fiber, acoustic material.